2008
DOI: 10.1103/physrevb.77.184110
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ba and Zr stability inUO2±xby density functional calculations

Abstract: Barium and zirconium behavior in nuclear fuels is investigated using density functional theory ͑DFT͒. More particularly, incorporation and solution energies of Ba and Zr in preexisting trap sites of UO 2 ͑vacancies, interstitials, U-O divacancy, and Schottky trio defects͒ are calculated using the projector-augmented-wave method as implemented in the Vienna ab initio simulation package ͑VASP͒. Correlation effects are taken into account within the DFT+ U approach. Our results are discussed in relation to those b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 63 publications
7
28
0
Order By: Relevance
“…between 1973 and 2173 K), some experimental observations seem to evidence the same thermodynamic behaviour [36] Ab initio calculations [42] have recently shown that incorporation of caesium in slightly hyperstoichiometric UO 2+x could be favoured in case of increase of uranium vacancy concentration which happens in fuel submitted to irradiation (exactly as for zirconium, as previously discussed). Nevertheless, incorporation (or solution) energy of caesium in uranium vacancy [42] is considerably lower than for zirconium [37]. For that reason, its behaviour is expected to be different from that of zirconium.…”
Section: Caesium Behaviourmentioning
confidence: 99%
“…between 1973 and 2173 K), some experimental observations seem to evidence the same thermodynamic behaviour [36] Ab initio calculations [42] have recently shown that incorporation of caesium in slightly hyperstoichiometric UO 2+x could be favoured in case of increase of uranium vacancy concentration which happens in fuel submitted to irradiation (exactly as for zirconium, as previously discussed). Nevertheless, incorporation (or solution) energy of caesium in uranium vacancy [42] is considerably lower than for zirconium [37]. For that reason, its behaviour is expected to be different from that of zirconium.…”
Section: Caesium Behaviourmentioning
confidence: 99%
“…In order to simplify the calculation of defect properties the latter two contributions are ignored in the present study. Recent reports have shown that the LDA/GGA+U methodology correctly describes many of the relevant properties of UO 2 and UO 2+x 42,[44][45][46][47][48][49][50][51][52][53][54][55][56] . In accordance with earlier LDA+U studies the U and J values were set to U = 4.5 eV and J = 0.51 eV 46 .…”
Section: Approachmentioning
confidence: 99%
“…In order to better describe the localization of the f electrons of uranium in this compound, the GGA+U functional can be considered [12,13]. Very recently, we showed that the use of GGA+U functional leads to a better agreement with experimental data for solution energies of fission products, namely Ba, Zr, Cs and Mo in urania [14][15][16]. In this contribution, we extend our calculations of solution energies with GGA+U functional to He and other important FP for safety like Kr, Xe, I, Te, Ru, Sr and Ce.…”
Section: Introductionmentioning
confidence: 96%